2013
DOI: 10.1128/aac.00970-13
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Reveals Genetic Diversity of Carbapenem- or Ceftazidime-Nonsusceptible Pseudomonas aeruginosa in China

Abstract: It is unclear whether the genetic background of drug-resistant Pseudomonas aeruginosa was disseminated from a certain clone. Thus, we performed MLST (multilocus sequence typing) of 896 P. aeruginosa isolates that were nonsusceptible to imipenem, meropenem, or ceftazidime. This revealed 254 sequence types (STs), including 104 new STs and 34 STs with novel alleles. Thirtythree clonal complexes and 404 singletons were found. In conclusion, drug-resistant P. aeruginosa clones can be developed from diverse genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…In Colombia, this ST has also been reported in an isolate harboring bla KPC-2 and bla VIM-2 , similar to one of the isolates harboring both genes found in this study (22). Previous studies in China and Spain have shown that clones of carbapenem-resistant P. aeruginosa can emerge from diverse genetic backgrounds and that MLST diversity could actually be higher than detected (29,30). In accordance with this, it appears that the population structure of carbapenem-resistant P. aeruginosa isolates in Colombia is also diverse, with several distinctive clones currently able to harbor KPC and VIM carbapenemases, mainly ST235 and ST111, respectively, but with the parallel emergence of other clones.…”
Section: Discussionmentioning
confidence: 51%
“…In Colombia, this ST has also been reported in an isolate harboring bla KPC-2 and bla VIM-2 , similar to one of the isolates harboring both genes found in this study (22). Previous studies in China and Spain have shown that clones of carbapenem-resistant P. aeruginosa can emerge from diverse genetic backgrounds and that MLST diversity could actually be higher than detected (29,30). In accordance with this, it appears that the population structure of carbapenem-resistant P. aeruginosa isolates in Colombia is also diverse, with several distinctive clones currently able to harbor KPC and VIM carbapenemases, mainly ST235 and ST111, respectively, but with the parallel emergence of other clones.…”
Section: Discussionmentioning
confidence: 51%
“…On the other hand, Ps. aeruginosa isolates show high diversity even in MLST analyses (Kidd et al 2011;Gomila et al 2013;Ji et al 2013). Although 70% of the isolates here were collected in one hospital, Simpson's index of the POT in this study was 0Á986.…”
Section: Discussionmentioning
confidence: 64%
“…; Ji et al . ). Although 70% of the isolates here were collected in one hospital, Simpson's index of the POT in this study was 0·986.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations